Dissemination of the Methicillin Resistant Staphylococcus aureus (MRSA) Pediatric Clone (ST5-T002-IV-Pvl+) as a Major Cause of Community Associated (CA) Staphylococcal Infections in Bedouin Children, Southern Israel. (4th October 2017) - Rokney, Assaf; Baum, Moti; Ben-Shimol, Shalom; Sagi, Orli; Anuka, Einav; Agmon, Vered; Greenberg, David; Valinsky, Lea; Danino, Dana
Abstract: Background: Pediatric CA-MRSA infections are emerging worldwide. High CA-MRSA carriage rates were previously described in healthy Bedouin children (Adler et al, J Clin Microbiol 2009). We assessed demographic, clinical and molecular characteristics of MRSA infections in children in southern Israel. Methods: Soroka University Medical Center microbiology laboratory serves the entire population of southern Israel, divided into two ethnic groups, Bedouin and Jews. All in-hospital MRSA isolates from children 0–18 years, obtained in 2016 were included. Clinical data were recorded from the hospital's computerized records. Health-care associated (HA) and community-associated infections were defined according to the US Center for Disease Control and Prevention. All isolates were evaluated for staphylococcal cassette chromosome (SCC mec ), Panton–Valentine leucocidin (PVL), S taphylococcus aureus protein A ( spa ) type as well as by pulsed-field-gel-electrophoresis (PFGE) and antimicrobial susceptibility testing. Results: Overall 95 (18%) of S. aureus isolates were MRSA (Table 1). Twenty-five different MRSA strains were identified. 28 isolates (29.5% of all MRSA) belonged to a pediatric clone, rarely observed in Israel (SCC IV, PVL positive, spa type 002; all demonstrate identical PFGE fingerprints). 82% of infections caused by this clone were community-acquired and were mainly observed in young Bedouin children, causing skin and soft-tissue infections (SSTI). Comparisons between the new clone and other CA-MRSA and HA-MRSA strains are shown in Table 1. All isolates of the pediatric clone were susceptible to TMP/SMX, ciprofloxacin, gentamicin, tetracycline, rifampicin and vancomycin; 17.8% were nonsusceptible to erythromycin and clindamycin (Table 2). Conclusion: The pediatric CA-MRSA clone, previously described only in sporadic cases in Israel, is emerging among previously healthy, young Bedouin children, typically causing SSTI. Isolates are susceptible to a variety of non-β lactam antibiotics. Disclosures: All authors: No reported disclosures.